Children's participation: moving from the performative to the social. Issue 3 (4th May 2017) - Horgan, Deirdre; Forde, Catherine; Martin, Shirley; Parkes, Aisling
Abstract : The body of work on children's participation has been valuable in asserting its importance. Nonetheless, participation is a contested concept and key challenges arise relating to its emphasis on age and voice, its focus on socialising the participative responsible citizen, and its failure to sufficiently recognise the range of participatory activities of children in their everyday lives. This article presents findings of a study on children's experiences of participation in their homes, schools, and communities including the importance of the relational context, how everyday interactions rather than 'performative' formal structures for participation are valued by children and how their participation is limited by adult processes based on notions of competence and voice. It concludes with an argument for recognising and facilitating children's informal and social participation as well as new forms of democratic processes being developed by children to address the possibility of governance and over-responsibilisation of children.